Lepton masses and mixing without Yukawa hierarchies (2006)
ABSTRACT: We investigate the neutrino masses and mixing patten in a version of the SU(3)c⊗SU(3)L⊗U(1)X model with one extra exotic charged lepton per family as introduced by Ozer. It is shown that an extended scalar sector, together with a discrete Z2 symmetry, is able to reproduce a consistent lepton mass spectrum without a hierarchy in the Yukawa coupling constants, the former as a carefull balance between one universal see-saw and two radiative mechanisms.